EFFECT OF SEX AND SLAUGHTER WEIGHT ON MEAT QUALITY OF BLACK GOAT AND MERIZ KIDS - Chinar S. Hassan; J. E. Alkass; I. A. Baker (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The objectives of this work was to study the effect of sex and weight at slaughter on meat quality in the longissimus muscle of Black goat and Meriz goat .Twenty four weaned kids from each breed were divided equally and penned individually into two groups .The 1st was castrated using rubber ring ,and the 2nd was left intact ,and was assigned to be slaughtered at 15,20 and 25 kg live body weight .The overall means of pH, lightness ,redness ,yellowness, drip loss, cooking loss and tenderness were 5.94±0.009 , 46±1.16 , 20.01±0.68 , 35.68±0.78 ,0.25±0.01, 12.17±0.35 ,1.65 ±0.008, respectively. Results revealed neither breed nor sex had a significant effect (p>0.05) on pH, color, drip loss, cooking loss and tenderness. It seems that kids slaughtered at 15 kg had more lightness, have more drip loss, and lower cooking loss as compared with kids slaughtered at 20 and 25 kg.